Desenvolvimento cultural transfronteiriço: um estudo sobre a cultura como protagonista no desenvolvimento regional na fronteira Brasil – Venezuela - Lourêto, Emanuel Henrique de Sousa (2016)
Culture and Development, two allocated terms, a priori, in different universes and unsociable, where the first is allocated an abstract plan and the second in concrete. When it sees a correlation between these two landmarks, it is theoretical frameworks for the proposal raised here of a cultural development. With this parameter set, respecting the Amazon developmental purpose of this graduate program establishes a geographical cut the border between Brazil and Venezuela, to address the potential of the city of Pacaraima in the cultural sector and it’s consequential to region. This dissertation brings a lot of discussions about the cultural factor as a force promoting development in the border region. Divided into three chapters, in which it sought to support a series of questions, theoretically basing the hypotheses. In the first chapter, the theoretical foundations are presented, the issues are addressed to general and development, border and culture. So with this theoretical framework established seeks to deepen the themes, matching them with the proposed study object. The second chapter in turn is more methodological matrix, in which is shown four-dimensional data model approach. In this chapter is introduced, sketched and designed the four dimensions in which it is seem as development in the border environment in question: the sociological, anthropological, economic and political. Finally, the last chapter sought to expose the data collected under the auspices of the four dimensions, plastering with theoretical parts to strengthen the proposed objectives.